UPDATING SPATIAL INFORMATION OF 27 MAMMAL SPECIES IN NEPAL - H. B. Katuwal; H. P. Sharma; P. J. L. Shaner; R. Gurung; V. Thapa; T. G. Magar; T. B. Gurung; K.; Parajuli; M. B. Gurung; H. Basnet; S. Koirala; et al. (Journal of Animal and Plant Sciences, 2018)
Information on species distribution range is a prerequisite for setting conservation strategies. Conservation efforts in Nepal have been focused on flagship species, such as Bengal Tiger ( Pantheratigris) , Asian Elephant (Elephasmaximus) and Greater One-horned Rhinoceros (Rhinocerosunicornis) . By contrast, distribution data and conservation efforts for other mammalian species are scarce. Here we documented the spatial locations of 27 mammal species based on direct sightings and photographic evidence from 70 m to 4,800 m of elevation across Nepal. We mapped their geographic distributions, delineated their elevation ranges and summarized the potential threats within their distribution ranges. We observed expanded elevation range forc. 30% of the 27 species ( 8 species), with the most noticeable upward expansion of the Common Palm Civet (Paradoxurushermaphroditus) from <1,500 m to 2,990 m, and downward expansion of the Fawn-colored Mouse (Muscervicolor) from >1,150 m to 200 m. These updated, high-quality spatial information on a subset of Nepalsdiverse mammalian fauna, highlight new opportunities to study the effects of climate change on mammals in the Himalayan region. and CsorbasMouse-eared Myotis (Myotis csorbai)
Keywords: altitudinal distribution; geographic distribution; range shift; threatened species; wildlife.